2023
DOI: 10.3389/fcogn.2023.1018096
|View full text |Cite
|
Sign up to set email alerts
|

Children's screentime is associated with reduced brain activation during an inhibitory control task: A pilot EEG study

Abstract: Children's screentime has been linked with a variety of behavioral consequences, including decreased inhibitory control. While children's screentime is associated with distinct functional brain differences, the links between screentime and neural markers of inhibitory control are unknown. Therefore, we examined these relationships in a pilot study using a Go/No-Go task (N = 20). After controlling for age, increased child screentime was significantly correlated with reduced P2 and P3 amplitudes elicited by No-G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Playing with a human opponent did not show this effect, suggesting that social interaction reduced distraction. Lewin et al (2023) (#30) examined the relationship between child screentime and neural processes for inhibitory control. They found that after controlling for age, increased screentime was associated with reduced P2 and P3 amplitudes elicited by No-Go trials, indicating less robust inhibition.…”
Section: -Negative Impactmentioning
confidence: 99%
See 2 more Smart Citations
“…Playing with a human opponent did not show this effect, suggesting that social interaction reduced distraction. Lewin et al (2023) (#30) examined the relationship between child screentime and neural processes for inhibitory control. They found that after controlling for age, increased screentime was associated with reduced P2 and P3 amplitudes elicited by No-Go trials, indicating less robust inhibition.…”
Section: -Negative Impactmentioning
confidence: 99%
“…First, this scoping review found that 23 studies reported the impact on children's brain functions: six positive effects, 15 negative impacts, and two mixed results. In particular, six EEG/ERP (Twait et al, 2019;Kostyrka-Allchorne et al,2019;Law et al, 2023;Lewin et al, 2023;Wetzel et al, 2021;Zivan et al, 2019), five fNIRS (Matsuda & Hiraki, 2006;Shimada & Hiraki, 2006;Li et al, 2019;Li et al, 2020;Li et al, 2021), and four fMRI (Baker et al, 2018;Chen et al, 2023;Horowitz & Hutton, 2017;Hutton et al, 2020) reported the negative effects of digital experiences on children's brain function. In contrast, two EEG/ERP studies (Mondéjar et al, 2016;Bergen et al, 2017), one fNIRS study (Li et al, 2017), and three fMRI studies (Han et al, 2007;Murray et al, 2006;Chaarani et al, 2022) reported the positive and training effects of digital experience on children's brain function.…”
Section: Whether Digital Experience Can Shape Young Mindsmentioning
confidence: 99%
See 1 more Smart Citation